Exploring the Self-Regulated Learning Skills of Physics Students in an Online Learning Environment - Malago, Jasruddin Daud; Mahande, Ridwan Daud; Setialaksana, Wirawan (Universitas Negeri Makassar, 2023)
This research investigates the factors of students' self-regulated learning (SRL) skills in online learning environments from the demographic perspectives of gender and major. The study employs a survey design and involves 103 students selected through simple random sampling. Data collection uses the SOL-Q questionnaire and observation. The collected data is analyzed using descriptive statistics, t-tests, and one-way ANOVA. The research results indicate that among the five components of SRL, the environmental structure obtained a high score, meaning that environmental structure contributes significantly to SRL in online learning for physics and non-physics majors. Meanwhile, time management received a low score, indicating that time management contributes less to SRL. There is no significant difference in each component of SRL based on gender and major. Furthermore, there is no significant effect of gender and major on the level of SRL